Mining towns and migration: Comparing three South African cases - Pretorius, Anmar; Blaauw, Derick (Frontiers in Sustainable Cities, 2023)
The South African economy has a long history of mining exploration. The first mining operations were recorded in 1852. Literature has expressed the need to continue exploring the implications of internal and cross-border in-migration on the labour market of destination areas. This paper investigates migration patterns in South Africa by focusing on three mining towns (Postmasburg, Rustenburg and Emalahleni) in three different provinces. Postmasburg is the only one that experienced recent periods of expansion. This is reflected in the significant increase in the number of migrants moving to Postmasburg during 2011 and 2012, and the shorter average length of stay of migrants in Postmasburg (7.2 years compared to 9.8 years in Emalahleni and 11.0 in Rustenburg). The results resonate with the neo-classical notion of self-interest among younger people as a motivating factor for migration. Migrants in our samples were significantly younger than the locally-born respondents and display higher levels of education. Empirical results confirm this positive return on increased education levels with a positive and highly statistically significant return to every additional year of formal education. In all three towns, the dummy variable included to represent a distinction between mineworkers and non-mineworkers was statically significant. This confirms the general perception that mineworkers in all these communities receive a premium in terms of their monthly earnings – even after controlling for different levels of education. As part of a future research agenda, the role of environmental factors as a driver of migration could also be investigated in depth in Southern Africa.